2008
DOI: 10.1136/vr.163.2.50
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for transplacental transmission of the current wild‐type strain of bluetongue virus serotype 8 in cattle

Abstract: infects fetuses, as suggested by the cerebral malformations observed by the authors, its biology would differ significantly from that of wild type BTV strains studied previously.To confirm, and examine the importance of, transplacental transmission of the current BTV-8 strain under field conditions, a total of 110 pairs of serum samples from cows and their calves were collected during caesarean sections,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 11 publications
(16 reference statements)
0
36
0
Order By: Relevance
“…The virus was spread by Palearctic midge species (Meiswinkel et al, 2008) and appeared to be highly virulent, causing clinical disease not only in sheep, but also in cattle and goats (Thiry et al, 2006;Dercksen et al, 2007;Dal Pozzo et al, 2009). It was also observed that infection of pregnant sheep and cattle resulted in a high incidence of reproductive failures including abortions, still births and malformations in offspring, suggesting that the virus had acquired the capability to cross the ruminant placenta (Wouda et al, 2008;Vercauteren et al, 2008;Desmecht et al, 2008). Prior to the European outbreak of BTV-8, transplacental infection had generally only been associated with the vaccination of pregnant sheep and cattle with egg and cell culture adapted modified-live virus (MLV) vaccines of South African and American origin (Kirkland and Hawkes, 2004), whereas wild-type strains were generally thought to be incapable of doing so.…”
Section: Several Characteristics Of the 2006-2008 Outbreak Of Btv-8 Imentioning
confidence: 99%
See 1 more Smart Citation
“…The virus was spread by Palearctic midge species (Meiswinkel et al, 2008) and appeared to be highly virulent, causing clinical disease not only in sheep, but also in cattle and goats (Thiry et al, 2006;Dercksen et al, 2007;Dal Pozzo et al, 2009). It was also observed that infection of pregnant sheep and cattle resulted in a high incidence of reproductive failures including abortions, still births and malformations in offspring, suggesting that the virus had acquired the capability to cross the ruminant placenta (Wouda et al, 2008;Vercauteren et al, 2008;Desmecht et al, 2008). Prior to the European outbreak of BTV-8, transplacental infection had generally only been associated with the vaccination of pregnant sheep and cattle with egg and cell culture adapted modified-live virus (MLV) vaccines of South African and American origin (Kirkland and Hawkes, 2004), whereas wild-type strains were generally thought to be incapable of doing so.…”
Section: Several Characteristics Of the 2006-2008 Outbreak Of Btv-8 Imentioning
confidence: 99%
“…Field surveys have indicated that the virus was extremely efficient at crossing the placenta. For example, transmission rates of 33-41% were recorded amongst calves born to previously infected dams in the field in the Netherland, Belgium and the United Kingdom (2007Kingdom ( -2008 (Darpel et al, 2009;De Clercq et al, 2008;Desmecht et al, 2008). The high frequency with which the BTV-8 strain was able to cross the placenta may have been a contributing factor that allowed the virus to persist during the adult vector free/low European winters.…”
Section: Several Characteristics Of the 2006-2008 Outbreak Of Btv-8 Imentioning
confidence: 99%
“…The BTV-8 strain also demonstrated the ability to cross the ruminant placenta a (Backx et al, 2009;Darpel et al, 2009;De Clerq et al, 2008;Desmecht et al, 2008;Menzies et al, 2008;Saegerman et al, 2010;van der Sluijs et al, 2011;Vercauteren et al, 2008), a property that had previously only generally been associated with the vaccination of pregnant animals with MLV strains (Flanagan and Johnson, 1995;Parsonson et al, 1987;Schultz and Delay, 1955).. The BTV-8 strain also appears to have had an increased tendency to be secreted in the semen of infected rams and bulls.…”
Section: Why Is It Important To Identify the Molecular Determinants Tmentioning
confidence: 95%
“…Thereafter, serum testing became recommended in Buenos Aires for acute febrile illness, among other dengue surveillance interventions in the area. More recently, epidemiologic surveillance of febrile illness has been strengthened countrywide upon the recent reporting of yellow fever cases in Argentina (8).…”
Section: Indigenous Denguementioning
confidence: 99%